Sarcoma of the sella after radiotherapy for pituitary adenoma - Berkmann, Sven; Tolnay, Markus; Hänggi, Daniel; Ghaffari, Anthony; Gratzl, Otmar (Acta neurochirurgica, 2010)
Secondary malignancies are infrequent sequelae of pituitary radiotherapy. The goal of the present case study is to analyze clinical features of a selected group of cases to define the special characteristics of these tumors. We report the illustrative case of a 38-year-old man with acromegaly who had transsphenoidal surgery and radiotherapy 7 years before presenting with a sellar high-grade sarcoma. Transsphenoidal and transcranial resection, as well as repeated gamma knife radiosurgery, could not prevent tumor progression and development of meningiosis sarcomatosa. We performed a thorough search of the literature and reviewed numerous publications and reports on primary and secondary sarcomas of the sella. Our search revealed 51 cases of mesenchymal malignancies after sellar radiotherapy. For further analysis, we identified and selected a group of patients based on the criteria for studying radiation-induced tumors as described by Cahan.Compared to the surgically treated group, secondary sarcomas of the sella are more frequent in patients who have had radiotherapy. These tumors occur at normal dose schedules with long latencies. Their growth is very aggressive and they may develop meningiosis sarcomatosa. Until now, no treatment modalities have been able to stop the progression of these neoplasms. Radiation-induced sarcoma is a rare sequela of pituitary radiotherapy. It is important for the treating physician to keep in mind the possibility of post-radiation sarcoma development. Additionally, one must include these tumors into the differential diagnosis in pituitary patients presenting with tumor recurrence more than 5 years after radiotherapy in combination with a secondary lack of hormonal activity.
Gesehen am 20.01.2023